PEMETAAN UPAYA PENINGKATAN PRODUKSI ASI IBU NIFAS BERBASIS ASUHAN KOMPLEMENTER : STUDI DESKRIPTIF - Rahmanindar, Nora; Prastiwi, Ratih Sakti; Qudrinani, Meyliya (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Efforts to increase milk production can be done by pharmacological and non-pharmacological methods. Non-pharmacological methods used to increase milk production are known as complementary care. The purpose of this study was to determine the crisis of increasing milk production in postpartum mothers based on complementary orphanages. This type of research is quantitative with a descriptive approach, the sampling technique is using an accidental sample. Data collection used a questionnaire which was distributed via google form, with 89 breastfeeding mothers as respondents. Results of the study Efforts to Increase Breast Milk Production for Postpartum Mothers were dominated by consuming vegetables every day as many as 86 people (96.6%), the results of the study most respondents did not consume dates 3 days every day as many as 65 people (75.0%), did not consume whole grains (almonds, cashew, edamame etc.) at most 56 people (62.9%), did not consume milk as many as 53 people (59.6%) and the least who consumed milk 36 people (40.4%), ASI Facilitator Capsules, the most postpartum mothers consume capsules 48 people (53.9%) increased breastfeeding, postpartum mothers consumed 74 people (83.1%) breastfeeding facilitating herbal medicine, consumed Chinese medicine, most postpartum mothers did not consume Chinese medicine for milk production, 84 people (94.4%) massaged the breasts for increased milk production by 46 people (51.7%), acupressure, most postpartum mothers did not do acupressure to increase milk production by 78 people (87.6%), acupuncture, most postpartum mothers did did not do acupressure to increase milk production as many as 84 people (94.4%).